Variability of grain oil content in the maize inbreds – carriers of endospermic mutations - Tymchuk, D.; Muzhilko, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The influence of interactions gene : genotype and genotype : environment on the grain oil content and the factor components of its module in the maize inbreds – carriers of endospermic mutations were studied. The highest average levels of grain oil content and the part of germ were inherent to the carriers of mutation sh2 and the highest levels of germ oil content – to the carriers of mutations su1 and se. These traits were notable as having the quantitative nature in the inbreds with the identical allelic state of each gene of endosperm structure and the manifestation of these traits depended on the inbred genotype and weather conditions of growth. The range of variability for the grain oil content in different inbreds – carriers of one mutation reached 2.7%, for the part of germ – 4.2% and for the germ oil content – 5.6%. The possibilities of identification of the inbreds which combined the increased part of germ with the increased content of germ oil as well as inbreds with the stable high levels of grain oil content and its factor components in different weather growing conditions were showed.